Evaluation of Nitric Oxide Concentrations in Preeclampsia and Normal Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
During pregnancy Nitric oxide is one of the most important relaxing factors for myometrium and also in the control of blood flow in uterus and placenta. Nitric oxide is generated by endothelial type II nitric oxide synthase (NOS) and acts as a vasodilator.Objective:To investigate the level of nitric oxide (NO) production in pregnancies complicated by preeclampsia and in normal pregnancy.Materials and Methods: A case control study was undertaken in Department of Gynaecology and Obstetrics of Bangabandhu Sheikh Mujib Medical University (BSMMU), from january to july 2014. The study population was pregnant women having preeclampsia and normal pregnancy who attended the OPD Department of Obstetrics and Gynecology in BSMMU between 29 to 40 weeks of gestation. As because of transient and volatile nature of nitric oxide, it was unsuitable to measure the nitric oxide level by conventional method. However, two stable break down product, nitrate (NO3 -) and nitrate (NO2 -) could be easily detected by sprectophototric means. Nitrate (NO2 -) was first converted to Nitrite (NO3 -) by reduction process using cadmium. Then concentration was measured by using Griess reagent in UV sprectophototric machine. This procedure was done in the Biochemistry Department, Dhaka University.Results: The mean nitrite level was found 18.37}3.64 mol/L in case group and 25.57}2.11mol/ L in control group, which was significantly (p